Hot Spot for a Large Deletion in the 18- to 19-Centisome Region Confers a Multiple Phenotype in Salmonella enterica Serovar Typhimurium Strain ATCC 14028 - Murray, Sean R. (American Society for Microbiology, 2004)
Loss of the Salmonella MsbB enzyme, which catalyzes the incorporation of myristate destined for lipopolysaccharide in the outer membrane, results in a strong phenotype of sensitivity to salt and chelators such as EGTA and greatly diminished endotoxic activity. MsbB(−) salmonellae mutate extragenically to EGTA-tolerant derivatives at a frequency of 10(−4) per division. One of these derivatives arose from inactivation of somA, which suppresses sensitivity to salt and EGTA. Here we show that a second mode of MsbB(−) suppression is a RecA-dependent deletion between two IS200 insertion elements present in Salmonella enterica serovar Typhimurium strain ATCC 14028 but not in two other wild-type strains, LT2 and SL1344, which lack one of the IS200 elements. This deletion occurs spontaneously in wild-type and MsbB(−) strain 14028 salmonellae and accounts for about one-third of all of the spontaneous suppressors of MsbB(−) in strain 14028. It spans the region corresponding to 17.7 to 19.9 centisomes, which includes somA, on the sequenced map of Salmonella LT2 (136 ORFs in that strain; ATCC 14028 and other strains showed variability in this region). In addition to conferring EGTA resistance correlated with somA, the deletion confers a MacConkey galactose resistance phenotype on MsbB(−) Salmonella, indicating that at least one additional gene (distinct from somA) within the deletion is responsible for this phenotype. In the wild type, the deletion mutant grows with normal exponential growth rate in Luria broth but is chlorate resistant and does not grow on citrate agar. The deletion strains have lost hydrogen sulfide production, nitrate reductase activity, and gas production from glucose fermentation.